2017
DOI: 10.1007/s11746-017-3028-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Drying Procedures on the Nutritional Value of the Mantle and Tentacles of Sepia officinalis

Abstract: The aim of this work was to investigate the influence of two different drying methods, traditionally by sun and controlled temperatures of 45, 50, 60 and 70 °C and relative humidity of 20 and 30% on the chemical composition of Sepia officinalis. When compared to fresh samples, lipid content increased under both drying methods whereas protein levels significantly increased only under controlled conditions. Drying procedures increased the percentage of saturated fatty acids mainly in sun‐dried samples and at hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…During sun drying, oxidation of fish lipids is facilitated by direct exposure to sunlight for a longer duration. Selmi et al (2010) compared the oxidative stability of silverside fish during sun drying and hot air drying and Tir et al (2017) compared the oxidation of sun-dried and hot air-dried cuttlefish. In both studies, significantly higher amounts of TBARS, PV, and free fatty acids were observed in sun-dried samples.…”
Section: Lipid Oxidationmentioning
confidence: 99%
“…During sun drying, oxidation of fish lipids is facilitated by direct exposure to sunlight for a longer duration. Selmi et al (2010) compared the oxidative stability of silverside fish during sun drying and hot air drying and Tir et al (2017) compared the oxidation of sun-dried and hot air-dried cuttlefish. In both studies, significantly higher amounts of TBARS, PV, and free fatty acids were observed in sun-dried samples.…”
Section: Lipid Oxidationmentioning
confidence: 99%
“…It presents high growth rates (Forsythe et al, 1994) and market price (FAO, 2008). In Tunisian coasts, little is known about S. officinalis and some works have discussed its systematic and reproduction cycle (Najai, 1983), genetic diversity (Tir et al, 2015a), chemical composition (Tir et al, 2015b), and also the effect of different drying procedures on the nutritional value (Tir et al, 2017).…”
Section: Introductionmentioning
confidence: 99%